Formulation and Characterization of Drug‐Loaded Microparticles Using Distillers Dried Grain Kafirin. Issue 3 (13th January 2015) - Lau, Esther T. L.; Johnson, Stuart K.; Stanley, Roger A.; Mereddy, Ram; Mikkelsen, Deirdre; Halley, Peter J.; Steadman, Kathryn J.
Abstract : Kafirin, a protein extracted from sorghum grain, has been formulated into microparticles and proposed for use as a delivery system owing to the resistance of kafirin to upper gastrointestinal digestion. However, extracting kafirin from sorghum distillers dried grains with solubles (DDGS) may be more efficient, because the carbohydrate component has been removed by fermentation. This study investigated the properties and use of kafirin extracted from DDGS to formulate microparticles. Prednisolone, an anti‐inflammatory drug that could benefit from a delayed and targeted delivery system to the colon, was loaded into DDGS kafirin microparticles by phase separation with sodium chloride. Scanning electron micrographs revealed that the empty and prednisolone‐loaded microparticles were round in shape and varied in size. Surface binding studies indicated prednisolone was loaded within the microparticles rather than being solely bound on the surface. These findings demonstrate DDGS kafirin can be formulated into microparticles and loaded with medication. Future studies could investigate the potential applications of DDGS kafirin microparticles as an orally administered targeted drug‐delivery system.